A Conceptual Model of Green Supply Chain Management Effects on Firm Performance - Hidayat, Reza; Crefioza, Omia; Kusuma, Pajar Damar; Habiibii, Yusuf Syahiir; Nur Fitria, Rafida; Nungkiastuti, Fauzia Damas; Rezqa Afifi, Fahmi (Institut Teknologi Sepuluh Nopember, 2020)
Green supply chain management (GSCM) is one of the strategies to overcome environmental problems caused by industrial activities and pressure from stakeholders such as the government and customers.The concept of green supply chain is a multidisciplinary issue that emerges essentially from building environment-friendly management practices in the context of supply chains. Nowadays manufacturing moves to Asia, awareness of green operations or sustainability has become important but relevant studies in Asian countries are not many especially in the Southeast Asia region .Prior studiesabout effects of GSCM on firm performance suggested for more in-depth research on the effect of each GSCM practices on company performance because GSCM's scope is quite extensive. Furthermore, several studies that examine the relationships between GSCM practices and organizational performance, there is a dearth of studies that have considered these relationships within the context of organizational or business strategy. Most studies have examined the outcomes of GSCM within the context of tangible measures such as environmental, operational, and economic performance. Consequently, research on intangible outcomes of GSCM practices is limited. Thus, the need examines the deployment of GSCMand analyzes their impact on environmental, economic and intangible performance.